Mediation in Paul’s Letter to Philemon - Fourie, Wynand (Stellenbosch Theological Journal, 2026)
Several aspects of Paul’s letter to Philemon form a part of the scholarly debate. This article suggests that valuable insights for ecclesial conflict management can be gathered from Paul’s approach in mediating a situation of conflict in the early church. The article argues from the social, cultural and inner texture of the letter to Philemon that Paul displays considerable mediation and rhetorical skill and intentionality in his attempt to appeal for a shift in attitude in Philemon from the perspective of his identity “into Christ” (v.6), “in Christ” (vv.8, 20), “in the Lord” (vv.16, 20) and “in Christ Jesus” (v.23) to “do even more than I ask” (v.21). Paul’s appeal to Philemon is, in the final instance, an “appeal of love” (Wright 2004:204).